2018
DOI: 10.1038/s41421-018-0022-5
|View full text |Cite
|
Sign up to set email alerts
|

Mtf2-PRC2 control of canonical Wnt signaling is required for definitive erythropoiesis

Abstract: Polycomb repressive complex 2 (PRC2) accessory proteins play substoichiometric, tissue-specific roles to recruit PRC2 to specific genomic loci or increase enzymatic activity, while PRC2 core proteins are required for complex stability and global levels of trimethylation of histone 3 at lysine 27 (H3K27me3). Here, we demonstrate a role for the classical PRC2 accessory protein Mtf2/Pcl2 in the hematopoietic system that is more akin to that of a core PRC2 protein. Mtf2−/− erythroid progenitors demonstrate markedl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 60 publications
(82 reference statements)
6
45
0
Order By: Relevance
“…We found that Wnt signaling was affected upon the loss of Mtf2. This is consistent with recent evidence that Mtf2 null mice demonstrated impairment in definitive erythroid development, and that Wnt was regulated by MTF2 during erythropoiesis 25 . We also found other signaling pathways (e.g.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…We found that Wnt signaling was affected upon the loss of Mtf2. This is consistent with recent evidence that Mtf2 null mice demonstrated impairment in definitive erythroid development, and that Wnt was regulated by MTF2 during erythropoiesis 25 . We also found other signaling pathways (e.g.…”
Section: Discussionsupporting
confidence: 93%
“…Reports on the phenotypic developmental consequences of losing PRC2 subunits during development have been diverse. The loss of Mtf2 has been shown to be embryonic lethal by E15.5, with observations of severe anemia and growth retardation [43][44][45] . On the contrary, Jarid2 null mice exhibited early embryonic lethality (as early as E10.5) [46][47][48] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In embryonic stem cells (ESC), MTF2 functions as a prototypical PRC2 accessory protein to recruit PRC2 to the extended pluripotency network gene promoters, leading to increased H3K27me3 methylation and repression of the pluripotency network to enable ESC differentiation (6). In contrast, in hematopoietic cells, MTF2 behaves more similarly to a core PRC2 component because its loss reduces SUZ12 and EZH1/2 expression and global H3K27me3 levels (8).…”
Section: Introductionmentioning
confidence: 99%
“…PRC2 is theorized to suppress Wnt signaling and thereby affect multiple biological processes, such as skeletal muscle differentiation [114], skeletal growth [115], adipogenesis [116], erythropoiesis [117], and intestinal homeostasis [118]. This suppression of Wnt signaling is mediated through a variety of targets within the Wnt pathway, including genes such as Wnt1, Wnt6, Wnt10a, Wnt10b, and Lef1.…”
Section: Prc2 Loss and Wnt Signalingmentioning
confidence: 99%